Kode Balinese Language Mixture, Campur Kode Bahasa Bali Tokoh Punakawan Wayang Kulit Parwa Dalam Cerita Rempong Bhisma - Ryandika, I Wayan Wira; Sangarsa, Ida Bagus Arthe Swara (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
This research aims to determine the mixture of Balinese language codes found in the punakawan wayang kulit parwa in the story Rempong Bhisma. The data source in this research is a video document of the Rempong Bhisma wayang kulit performance. Data collection methods in this research used socument study, interviews, and literature methods. The theories used to dissect the problem in this research are, Code Mixing Theory and Language Contact Theory. In this era of globalization whare technology and information are growing. Which causes the Balinese language to mix with other languages. Knowledge of two or more languages creates new language touch or contact, which causes a one language phenomenon called code mixing. One of them is the mixed code of Balinese wayang kulit parwa in story Rempong Bhisma. This research is a video documentation of the wayang kulit story Rempong Bhisma. The result of this research is the form of code mixing in the use of Balinese in language by the wayang kulit parwa in story Rempong Bhisma in the form of words, phrases, and sentence forms